Reproductive behavior of Chroicocephalus cirrocephalus (Vieillot, 1818) (Charadriiformes: Laridae) and Coragyps atratus (Bechstein‎, 1793) (Cathartiformes: Cathartidae) in the coastal wetland of humedal Villa, Lima, Peru - Amanqui-Aquino, Edson (2023)
Th e Villa Wetland, located in Lima, Peru, hosts a remarkable diversity of fauna, with a particular emphasis on avifauna. Th e reproduction of birds is a crucial element in the natural history of these species, making studies essential to guide conservation and management strategies for both bird populations and the ecosystems they inhabit. Th e objective of this study was to characterize and evaluate reproductive aspects of the Gray-hooded Gull [Chro icocephalus cirrocephalus (Vieollot 1818)] and the Black-headed Hen [Cora gyps atratus (Bechstein, 1793)], such as the biometry of nests, eggs and reproductive behavior. Nest monitoring was carried out between the months of May to September 2023. For C. cirrocephalus, 12 nests were found in patches of “sweet grass” Paspalum vaginatum Sw.; while, for C. atratus, four nests were recorded at the base of “molle costeño” Schinus terebinthifolia G. Raddi trees. For both species, the development of chicks into juveniles was observed. Likewise, an ethogram of behaviors was carried out for both species. For C. cirrocephalus, a total of 40 specifi c behaviors were recorded, with the category of “reproduction and parental care” being the most important during incubation; while, for C. atratus, a total of 27 specific behaviors were recorded, with the “alert” category being the most important among adult and juvenile individuals. Sw.; while, for C. atratus, four nests were recorded at the base of “molle costeño” Schinus terebinthifolia G. Raddi trees. For both species, the development of chicks into juveniles was observed. Likewise, an ethogram of behaviors was carried out for both species. For C. cirrocephalus, a total of 40 specific behaviors were recorded, with the category of “reproduction and parental care” being the most important during incubation; while, for C. atratus, a total of 27 specific behaviors were recorded, with the “alert” category being the most important among adult and juvenile individuals.